Life table variations in Wolbachia-transinfected (wMel & wAlbB strains) and uninfected Aedes aegypti: the role of various larval diets - Gunasekaran, Yazhini; Pachalil Thiruvoth, Vidhya; Annamalai, Sakthivel; Balakrishnan, Vijayakumar; Nagarajan, Shriram Ananganallur; Rahi, Manju (Frontiers in Insect Science, 2025)
IntroductionWolbachia-based vector control strategies have been successfully implemented as a sustainable long-term solution and a promising tool for controlling Aedes mosquitoes, primarily Ae. aegypti, the main vector of major arboviral diseases. Since it is essential to rear healthy and competent adult mosquitoes for mass release under Wolbachia-based vector control strategies, optimising larval diet is essential. Therefore, the current study tested and compared four different larval diets to examine their statistical significance on the Wolbachia transinfected and uninfected Ae. aegypti life table traits.MethodsWe tested and compared the effects of four larval diets: LD1 (fish feed), LD2 (laboratory rodent diet), LD3 (mushroom powder), and LD4 (dog biscuit plus brewer’s yeast) on hatchability, pupation, adult emergence, fecundity, and adult survival of Wolbachia-transinfected (wMel and wAlbB) Puducherry strains, as Among the tested diets, fish feed (LD1) and the combination of dog biscuit with brewer’s yeast (LD4) have significant effects in both Wolbachia-transinfected and uninfected Ae. aegypti strains regarding egg hatchability, pupation, adult emergence, fecundity, and adult survival.ResultsThe highest fecundity was observed under LD1 for uninfected Ae. aegypti, with approximately 84 eggs/female (84.0 ± 6.0), followed by wMel (Pud) mosquitoes ( 78 eggs/female, 78.0 ± 5.2) and uninfected mosquitoes ( 75 eggs/female,74.6 ± 23.3) under LD4 diet in the F0 generation. The uninfected Ae. aegypti females exhibited significantly lower mortality risk under LD2 (Hazard Ratio (HR)=0.56<1, P<0.001), with a high median survival of 57 days compared to all other diets.DiscussionThe results of this study suggest that LD1 (fish feed) can be recommended as the superior larval diet for the mass rearing of Wolbachia-transinfected strains, although both LD1 and LD4 diets demonstrated positive effects on all the Ae. aegypti strains. Meanwhile, LD4 (dog biscuit + brewer’s yeast) can be recommended for the routine rearing of uninfected Ae. aegypti colonies, as it is comparatively cost-effective and readily available in India. These findings could contribute to the large-scale mosquito rearing programs under the Wolbachia strategy, ultimately supporting the implementation of sustainable vector control approaches for arboviral disease management.